Sometimes even apoptosis fails: implications for cancer. (1st November 2020) - Berthenet, Kevin; Weber, Kathrin; Ichim, Gabriel
ABSTRACT: Apoptosis is vital for the correct morphogenesis of multi-cellular organisms. However, like most physiological programs, the cell's ability to commit suicide is hijacked by cancer in its own proliferative and invasive interest. We recently showed that inefficient execution of apoptosis (or failed apoptosis) is used by cancer to boost invasiveness.